Songs and Tales of the Arimi of Tanzania - Olson, Howard S. (International Library of African Music, 1982)
The following article contains five songs of the Arimi of Tanzania. Tales told in connection with the first two songs are included here, and a brief explanation of the background of the other three songs precedes them. The translations into English are rather free. It is traditional in Arimi society for several households to get together after the evening meal for a bit of fun and fellowship. Usually a number of riddles are told after which folk tales preserved in songs are led by various members of the group until everyone is tired enough to go to bed. After the song is sung its tale is related by the leader.
Keywords: Songs; Tales; African Music; Tanzania